The Impact of Abortion Restriction Laws on Female Labour Force Participation in USA - Andrieieva, Kateryna; Miklánek, Tomáš; Kalíšková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
The diploma thesis aims to examine the effect of regressive abortion laws on female labour market participation in U.S. Twenty-eight states enacted Targeted Regulation of Abortion Provider (TRAP) law, which impose restrictions on abortion providers and include licensing fees, physical plant/personnel regulations etc. By using yearly data, collected primarily from the Bureau of Census for survey years 2009 through 2016 and difference-in difference methods, the results show a significant negative impact of abortion restrictive laws on female labour market participation. However, show that support for the parallel trend assumption is weak. In this case, the causality of these estimations should be interpreted carefully. The effect of restrictive abortion laws led female labour market participation to fall by 1.3 percent. This decrease is comparatively small change in the mean of the dependent variable. The possible explanation of the result can be as follows: women living in the state with restrictive abortion laws would travel to a different county or state to access abortion services, other women would prevent the pregnancy by increasing the use of contraception instead of seeking abortion and hence not drop out from the labour market.
Vedoucí práce: Tomáš Miklánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses